2022
DOI: 10.1002/jad.12075
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: The association between emotional intelligence and subjective well‐being in adolescents

Abstract: Introduction Emotional intelligence (EI) is a psychological protective factor that can improve subjective well‐being (WB) in adolescents. This study aims to establish the overall relationship between different EI models (performance‐based ability model, self‐report ability model, and self‐report mixed model) and subjective WB in adolescents, analyze the affective WB and cognitive WB components, and examine the moderating effect of EI models on both types of subjective WB. Method We searched PsycINFO and WOS da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 87 publications
2
31
0
6
Order By: Relevance
“…In the social domain, emotions have an essential role to play in social interactions and especially the ability to manage one’s emotions becomes an important skill for initiating and maintaining peer relationships [ 54 ]. In this sense, emotional competencies influence peer relationships [ 55 ] and adolescents with higher emotional skills may maintain more positive and healthy social interactions [ 56 , 58 ]. In line with suggestions from previous studies [ 47 , 48 ], these results reveal the importance of developing emotional competence during adolescence to prevent the emergence of conduct problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the social domain, emotions have an essential role to play in social interactions and especially the ability to manage one’s emotions becomes an important skill for initiating and maintaining peer relationships [ 54 ]. In this sense, emotional competencies influence peer relationships [ 55 ] and adolescents with higher emotional skills may maintain more positive and healthy social interactions [ 56 , 58 ]. In line with suggestions from previous studies [ 47 , 48 ], these results reveal the importance of developing emotional competence during adolescence to prevent the emergence of conduct problems.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, emotional competencies influence peer relationships [ 55 ]. Thus, adolescents with higher emotional competence develop better interpersonal and social skills, have more friends and establish healthier and positive social relationships [ 56 , 57 , 58 ]. In contrast, adolescents with poor emotional skills have fewer resources to deal with interpersonal conflicts and use aggression to solve problems [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control and manage emotions makes teachers satisfied with their lives, and it drives subjective well-being (Katana et al, 2019). Previous studies have shown that EI and subjective well-being are interrelated (Llamas-D ıaz et al, 2022;Ngui and Lay, 2020;Austin et al, 2010). Teachers with high EI can adopt a positive coping style when facing pressure, thereby improving their subjective wellbeing (Villanueva et al, 2022;Kouhsari et al, 2022b;Gallagher and VellaBrodrick, 2008).…”
Section: Link Teachers' Subjective Well-being With Teachers' Ei and T...mentioning
confidence: 99%
“…In terms of mental health, it is essential to consider the relationship between EI and other psychological variables, not only the negative ones but also those indicative of positive mental health. Among these, the literature has pointed to life satisfaction and psychological well-being ( Salguero et al, 2012 ; Llamas-Diaz et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%